2010
DOI: 10.1136/jcp.2010.083550
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic vessel density and its prognostic value in stage I colorectal carcinoma

Abstract: AimsThe assessment of lymphatic vessel density (LVD) has been suggested as a tool to determine the metastatic risk of neoplasias. On this premise, the authors aimed to verify whether progression risk of stage I colorectal cancer may be related to LVD. The authors also evaluated and correlated vascular endothelial growth factor (VEGF)-A expression with LVD revealed in the same cases in order to investigate its potential lymphangiogenic role in the early stage colorectal cancer.MethodsLVD and VEGF immunoexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 43 publications
2
24
1
3
Order By: Relevance
“…The use of a specific lymphatic endothelial marker as D2-40 allows an accurate identification of the lymphatics, avoiding the misinterpretation of blood microvessels as lymphatics. We found a significant difference between PLVD and ILVD with a higher PLVD, in accordance with other reports [23][24][25][26][27][28][29][30][31][32][33] with the exception of the study of Longatto-Filho et al [34]. Moreover, the morphology of lymphatics is different between the two areas, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…The use of a specific lymphatic endothelial marker as D2-40 allows an accurate identification of the lymphatics, avoiding the misinterpretation of blood microvessels as lymphatics. We found a significant difference between PLVD and ILVD with a higher PLVD, in accordance with other reports [23][24][25][26][27][28][29][30][31][32][33] with the exception of the study of Longatto-Filho et al [34]. Moreover, the morphology of lymphatics is different between the two areas, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…LVI was also the only parameter to independently be associated with an adverse effect on disease specific survival. Some studies have shown LVD to be prognostic and associated to poor outcome or LNM [8,38] however others show that no correlation exists [9,39]. LVD assessment is, however, not standardised and most researchers employ various magnifications and numbers of LVD “hot-spots” utilised to create a mean LVD while observer variability has been shown to be strong [9].…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of original studies, systematic and meta-analysis reviews have been published on the subject of lymphatic vessel invasion (LVI) [5-7], lymphatic vessel density (LVD) [8-10] and tumour budding (TB) [11-15] in CRC prognosis [16,17]. A number of these have concentrated on early stage disease and the ability to utilise histopathological features to predict lymph node metastasis or to stratify patients at high risk of disease recurrence and poor outcome [6,9,16,18-22].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are inconsistent results regarding the relationships of LMVD with the clinicopathological parameters of CRC, such as tumor stage, degree of differentiation, and distant metastasis 8-20. We speculate that these discrepancies might be due to the using different antibodies and lacking standardization for the assesment of LMVD.…”
Section: Relationship Between Lymphatic Microvessel Density (Lmvd) Anmentioning
confidence: 91%
“…In an investigation of 52 stage CRC patients, Barresi et al20 reported that a high density of LMVD was significantly associated with the progression of stage I colorectal carcinoma. Gao et al19 reported that LMVD was reversely related to Dukes’ stage of CRC, it was significantly lower in tumors of Dukes’ stage C + D than in those of Dukes’ stage A + B. Eirik et al25 suggested that lymphangiogenesis is initiated before the tumor reaches stage II by examining LMVD in 18 paired samples of CRC tissues and normal mucosa.…”
Section: Lymphangiogenesis May Be An Early Event In Crc Developmentmentioning
confidence: 99%